2015
DOI: 10.1007/s10853-015-9199-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel felt pseudocapacitor based on carbon nanotube/metal oxides

Abstract: This work describes a novel supercapacitor electrode based on a glass fiber felt substrate, single-walled carbon nanotube (SWCNT) and metal oxide layers (RuO 2 or MnO 2 ). It is fabricated by the repeated and alternate deposition of SWCNTs and metal oxides via dipping and electrodeposition, respectively, to achieve three-dimensional layered hierarchical structured supercapacitor electrodes. The results show that the layered structured electrodes fabricated by alternating deposition of SWCNTs and metal oxides h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Thus, the glaring prospect of fabricating carbon-based nanomaterials from renewable sources could possibly satisfy the energy demand of the 21st century, hence replacing the fossil fuel sources. The quality and the recharge time of supercapacitors, supercapacitors-battery hybrids and lithium batteries have been experimentally tested to be enhanced using carbon nanotubes [ 169 , 170 , 171 ], graphene and activated carbon [ 79 ], etc. It has been reported that porous graphene oxide when tested gave ultra-high capacitances of 283 Farads/gram and 234 Farads/cm 3 .…”
Section: Applicationsmentioning
confidence: 99%
“…Thus, the glaring prospect of fabricating carbon-based nanomaterials from renewable sources could possibly satisfy the energy demand of the 21st century, hence replacing the fossil fuel sources. The quality and the recharge time of supercapacitors, supercapacitors-battery hybrids and lithium batteries have been experimentally tested to be enhanced using carbon nanotubes [ 169 , 170 , 171 ], graphene and activated carbon [ 79 ], etc. It has been reported that porous graphene oxide when tested gave ultra-high capacitances of 283 Farads/gram and 234 Farads/cm 3 .…”
Section: Applicationsmentioning
confidence: 99%
“…Each property of the synthesized AAFQDs nds multiple applications in innumerable domains. The applications include biological imaging, 54 drug/gene delivery, 55 antibacterial and antioxidant activity, 12 photoluminescence sensors, [56][57][58] electrochemiluminescence sensors, 59 catalysts in the organic synthesis of materials, 60 electrochemical sensors, 61,62 supercapacitors, 63 and batteries. 64 Various applications of AAFQDs are illustrated in Fig.…”
Section: Applications Of Functionalized Qdsmentioning
confidence: 99%
“…Fei et al [85], reported that nano-platelets of hydrothermally fabricated quantum dots, synthesized on graphene substrate gave excellent electro-catalytic effectfar better than the expensive platinum. As per the application to super-capacitors, Abbas et al [86], Ji et al [38] and Fam et al [87] have demonstrated the use of carbon nanotubes and graphene in composite form or as surface coating, for use as electrodes, to boost the capacitance of super-capacitors up to five times their usual values. Nanotubes of carbon have also been used for miniature transistors and highly conducting tiny wires [88].…”
Section: Some Notable Applications Of Carbon Nanomaterialsmentioning
confidence: 99%